Pemurnian Biogas Dari Gas Pengotor Hidrogen Sulfida (H2S) Dengan Memanfaatkan Limbah Geram Besi Proses Pembubutan - Komang Metty Trisna Negara; Tjokorda Gde Tirta Nindhia; I Made Sucipta; I Ketut Adi Atmika; Dewa Ngakan Ketut Putra Negara; I Wayan Surata; A.A.I.A. Sri Komaladewi (Department of Mechanical Engineering, University of Udayana, 2012)
This research is intended to utilize waste steel chips from the process of turning (process in which lathemachine is used) for purification of biogas from the gas of hydrogen sulfide (H2S) contaminant to supportthe promotion of zero waste industrial and manufacturing process in the world. The waste of Iron chips iscollected and selected. Only long and spiral like of iron chips that are useful for this purpose. Since thechips having residual stress due to strain hardening during turning process, then the annealing processshould be done before compacting to form a billet.The thickness of the billet was 1 cm and 6 cm indiameter with weight 500 gram. The annealing proces was carried out by burning the iron chip until reachthe red color of fire. During the annealing process the iron inside the steel will react with oxygen to formiron oxide (Fe2O3) and if during oxidation there is a water vapor in the air then the iron bog ore Fe(OH)3 willbe formed. Both of Fe2O3 and Fe(OH)3 are very reactive to H2S and therefore able to eliminate the H2Scontaminant inside the Biogas. The billet is used as a filter and to be installed in the line of biogasdistribution. The result indicate that the the iron chips is potential to be utilized to reduce the H2Scontaminant in the biogas